Tinjauan Fiqh Muamalah Terhadap Transaksi Multi Akad dalam Fatwa DSN-MUI Tentang Pembiayaan Likuiditas Jangka Pendek Syariah - Haerul Akmal; Mohammad Hanief Sirajulhuda (AL-ISTINBATH : Jurnal Hukum Islam, 2019)
The purpose of this study is to find out the multi-contract picture in the al-bai maa al-wad bi al-syira (BMWBS) agreement on the fatwa of the National Sharia Council of the Indonesian Ulama Council (DSN-MUI) Number 109/DSN-MUI/II/2017 concerning Sharia Short-Term Liquidity Financing (fatwa 109-PLJPS) and knowing multi-contract transactions in the BMWBS contract on 109-PLJPS fatwa from the perspective of muamalah fiqh. The research is a library research that is qualitative-descriptive in nature with a juridical-normative approach through deductive methods. The results obtained: First, the multi-contract in the BMWBS contract can be seen from several things; binding wa'd (promise) that links the two Sharia Securities transactions (SBS) between Sharia Banks and Bank Indonesia, time limits on SBS sale and purchase, and time-limited utilization of SBS ownership. Secondly, there is relevance between the hadith of the bay'ataini fi bay'ah and the BMWBS contract through illat riba. For this reason, DSN-MUI needs to review the 109-PLJPS fatwa by including the hadith of the bay'ataini fi bay'ah, then making it a legal consideration by looking at the various meanings of the ulemas and their agreement on it to make it more compatible with your fiqh.